The experience of midwives in performing episiotomy during birth - Muda, Siti Mariam (2018)
Objectives: The aim of the study is to explore the experience of midwives while performing episiotomy during vaginal birth. Design: Qualitative Individual face to face interviews using purposive sampling had been conducted. Semi structured questionnaire based on research question were used to guide this study to explore the factors identified for midwives performing episiotomy in the labour room. 15 midwives who fulfilled the inclusion criteria were interviewed and the sessions were audio taped, transcribed and identify for the themes. Recruitment took place at one of the government hospital in Malaysia. The main ethical issues highlighted were ethical approval, informed consent, confidentiality and anonymity. Findings: Based on thematic analysis four themes were emerged: 1) Structure of the perineum, 2) Maternal preference, 3) Influence of health care professional, 4) Midwives instinct. Conclusion: Majority of midwives are still performing episiotomy despite of the guidelines mentioned on the restrictive of the episiotomy practice. Midwives need to update themselves and familiar with evidence based practice in order to maintain intact perineal during childbirth. It is recommended for nurses and midwives to keep continuously involved in nursing or medical education regarding childbirth.